Method for regeneration of arsenic-poisoned catalyst, regenerated catalyst and use thereof
Patent Information
- Application Number
- CN202611203680.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-09-15
Smart Images

Figure CN122745971A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of waste catalyst resource recycling technology, and in particular to a method for regenerating arsenic-poisoned catalysts, as well as the regenerated catalyst and its application. Background Technology
[0002] Nitrogen oxides (NO) x NO is one of the main sources of air pollution. Selective catalytic reduction (SCR) technology is currently the most widely used method for detecting NO. x In emission control technologies, V2O5-WO3 / TiO2 denitrification catalysts are the main industrial catalysts for this technology. However, during long-term operation, As2O3 vapor in the flue gas irreversibly poisons the catalyst, causing the NO conversion rate to drop below 30%. Statistics show that millions of tons of SCR catalysts are scrapped annually due to arsenic poisoning, classifying them as hazardous waste requiring strict management.
[0003] Existing methods for regenerating poisoned catalysts all follow a sequential logic of "removal first, then repair." Acid washing utilizes inorganic acids to dissolve arsenic species, but it also dissolves active components like vanadium and tungsten, leading to the loss of active sites. Thermal treatment methods (such as calcination and hydrogen reduction) can partially remove arsenic, but high-temperature treatment causes the catalyst's pore structure to collapse and its specific surface area to decrease. While plasma treatment can remove arsenic at lower temperatures, it leaves dangling bond defects, which actually impair catalytic performance. Alkaline washing has some selectivity for arsenic, but strongly alkaline conditions can still corrode the catalyst framework.
[0004] However, after arsenic enters the catalyst in the form of As₂O₃ vapor, it is oxidized to As₂O₅ and replaces the oxide framework, forming As-OV and As-OW complexes. The As-O poison bond is difficult to distinguish from the vanadium-oxygen (VO) and tungsten-oxygen (WO) bonds in the framework based on traditional chemical properties such as solubility, volatility, and reducing power. This is the fundamental reason why traditional regeneration methods (acid washing, heat treatment, etc.) cannot selectively remove arsenic. Moreover, due to the lack of selective recognition ability, more thorough poison removal inevitably leads to more severe framework damage. Therefore, regeneration methods based on the "removal first, repair later" sequential logic (acid washing, heat treatment, alkaline washing, plasma) can achieve activity recovery (usually 80-98% of the activity of fresh catalyst), but they inevitably damage the framework while removing arsenic, resulting in a loss of 10-15% of vanadium and tungsten per cycle, and cannot surpass the performance baseline of fresh catalyst. This is not a defect of any specific method, but rather an inherent physical boundary of the "removal first, repair later" sequential paradigm.
[0005] Therefore, there is an urgent need to develop a catalyst regeneration method that can selectively remove arsenic poisons while avoiding skeletal damage, and even surpass the performance of fresh catalysts. Summary of the Invention
[0006] The purpose of this invention is to provide a method for regenerating arsenic-poisoned catalysts, as well as the regenerated catalyst and its application. The method utilizes polytetrafluoroethylene (PTFE) grinding beads and a PTFE grinding jar for ball milling. The arsenic-poisoned denitrification catalyst is selectively regenerated through the electroshear effect generated at the PTFE-PTFE friction interface. This method can selectively remove arsenic poisons while avoiding damage to the skeletal structure, and obtain a regenerated catalyst with activity exceeding that of the fresh catalyst.
[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for regenerating an arsenic-poisoned catalyst, comprising the following steps: A mixture of arsenic poisoning catalyst and hydrogen peroxide solution was placed in a polytetrafluoroethylene ball mill jar, polytetrafluoroethylene ball milling beads were added, and the mixture was ball milled to obtain the ball milled product. The ball milling product is separated from the ball milling beads, and the resulting solid product is washed and dried sequentially to obtain the regenerated catalyst.
[0008] Preferably, the hydrogen peroxide solution has a mass concentration of 1-15% and a pH value of 7-11.
[0009] Preferably, the solid-liquid ratio of the arsenic poisoning catalyst to the hydrogen peroxide solution is 1 g:(5~20) mL.
[0010] Preferably, the diameter of the polytetrafluoroethylene grinding beads is 4~10 mm.
[0011] Preferably, the mass ratio of the polytetrafluoroethylene grinding beads to the mixed material is 10~20:1.
[0012] Preferably, the ball milling speed is 300~400 rpm; the ball milling time is 120~180 min.
[0013] Preferably, the drying temperature is 100~120°C and the time is 8~16 h.
[0014] The present invention provides a regenerated catalyst obtained by the regeneration method described in the above technical solution.
[0015] This invention provides the application of the regenerated catalyst described in the above technical solution in the field of denitrification.
[0016] This invention provides a method for regenerating arsenic-poisoned catalysts. The invention utilizes the PTFE-PTFE friction interface to simultaneously generate mechanical shear force and triboelectric field during ball milling. The synergistic effect of these two forces achieves selective cleavage of the As-O poison bond, synchronous reconstruction of the VOW active bridge bond, and doubling of the acid sites in the regenerated catalyst. This eliminates the "damage window" in traditional serial regeneration methods, enabling the regenerated catalyst to outperform the baseline of the fresh catalyst.
[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) Pioneering "cut-end sealing" synchronous mechanism: Traditional regeneration methods require additional steps (impregnation, calcination) to rebuild active sites after removing toxins, and the skeleton is inevitably damaged during this "damage window". This invention utilizes PTFE-assisted ball milling to simultaneously complete the condensation reconstruction of VOW bridge bonds in the same collision event of cutting As-O bonds, fundamentally eliminating the damage window.
[0018] (2) Achieving "super-repair" beyond that of fresh catalysts: Existing regeneration methods all limit the recovery of fresh catalyst activity to the upper limit (80-98%). This invention is the first to obtain a regenerated catalyst with activity exceeding the baseline of fresh catalysts. The NO conversion rate exceeds the baseline of fresh catalysts by 34.7% throughout the entire reaction temperature range (200-400℃), and the number of strong acid sites exceeds that of fresh catalysts by 95.4%. This is not a "repair" of the catalyst, but a "reengineering".
[0019] (3) Dual-channel selectivity ensures skeleton integrity: This invention achieves accurate identification of As-O bonds through two positive communication channels: "structural selectivity" (shear force concentration caused by arsenic cluster phase separation) and "electronic selectivity" (difference in polarizability of different orbitals due to triboelectric field), solving the fundamental problem of "chemical indistinguishability" in traditional methods.
[0020] (4) A universal safety window criterion was established: Density functional theory (DFT) calculations determined that there is a thermodynamic energy gap of approximately 1.88 eV between the As-O bond and the VO / WO framework bond. Theoretically, selective surface editing can be performed by electroshearing when the bond energy difference between any poison-framework pair exceeds approximately 1.5 eV, providing a universal guiding principle for the design of regeneration methods for similar catalysts.
[0021] (5) Safe and mild operating conditions: This invention operates at room temperature and normal pressure, using PTFE grinding beads and PTFE grinding jars (chemically inert) and low concentrations of H2O2, without the need for strong acids, strong alkalis, or high-temperature treatment. The PTFE-PTFE friction interface spontaneously generates a triboelectric field without an external electric field. Agate control experiments demonstrate that the catalyst activity cannot be recovered without a triboelectric field, indicating that the selectivity originates from the physical mechanism of the PTFE-PTFE friction interface rather than the chemical oxidation of H2O2.
[0022] (6) Significant industrial economics: Verified by eight types of industrial waste catalysts, the regeneration cost is low, and CO2 emissions are reduced by 73% compared to the traditional acid washing method. Under the optimal condition of ball milling time of 150 min, the arsenic removal rate reaches 92%, the vanadium loss rate (1.7%) is lower than the baseline of fresh catalyst (2.1%), and the tungsten loss rate (1.3%) is comparable to that of fresh catalyst (1.4%). Attached Figure Description
[0023] Figure 1 This is a schematic flowchart of the regeneration method for the arsenic-poisoned catalyst of the present invention; Figure 2 XRD patterns of the fresh catalyst and the catalyst before and after regeneration in Example 1; Figure 3 A comparison chart of NO conversion rates for fresh catalyst (F-VWT), arsenic-poisoned catalyst (As-VWT), and catalysts obtained by different regeneration treatment methods in Comparative Examples 1-5 and Example 1; Figure 4 This is a comparison diagram of the electric field strength generated during the ball milling process of agate in Comparative Example 1 and polytetrafluoroethylene in Example 1; Figure 5 NO conversion rates of the fresh catalyst (F-VWT) and the catalyst before and after regeneration in Example 1; Figure 6 The amount of ammonia desorption is measured at different temperatures for the fresh catalyst and the catalyst before and after regeneration in Example 1. Figure 7 The graph shows the NO conversion rate after regeneration of waste catalysts from V2O5-WO3 / TiO2 honeycomb SCR denitrification in eight different factories. Detailed Implementation
[0024] In this invention, unless otherwise specified, the raw materials or reagents required for preparation are all commercially available products well known to those skilled in the art.
[0025] like Figure 1 As shown, the present invention provides a method for regenerating an arsenic-poisoned catalyst, comprising the following steps: A mixture of arsenic poisoning catalyst and hydrogen peroxide solution was placed in a polytetrafluoroethylene ball mill jar, polytetrafluoroethylene ball milling beads were added, and the mixture was ball milled to obtain the ball milled product. The ball milling product is separated from the ball milling beads, and the resulting solid product is washed and dried sequentially to obtain the regenerated catalyst.
[0026] In the arsenic poisoning catalyst of the present invention, arsenic exists in a phase-separated form in the form of clusters on the catalyst surface, which is incompatible with the TiO2 lattice; vanadium and tungsten are embedded in the catalyst framework, so that the mechanical shear force generated by ball milling is selectively concentrated at the interface between the arsenic clusters and the framework.
[0027] The arsenic poisoning catalyst described in this invention is derived from laboratory preparation or industrial waste catalyst, wherein the industrial waste catalyst is derived from SCR denitrification catalyst discarded from coal-fired power plants, and the As content is 1~5 wt%.
[0028] This invention does not specifically limit the composition of the arsenic poisoning catalyst; any industrial waste catalyst known in the art after arsenic poisoning is acceptable, with V2O5-WO3 / TiO2 SCR arsenic poisoning catalyst being more preferred. In the embodiments of this invention, the arsenic poisoning catalyst is prepared in the laboratory and then regenerated.
[0029] In this invention, the preferred laboratory preparation method for the V2O5-WO3 / TiO2 SCR arsenic poisoning catalyst is as follows: using anatase TiO2 as a support, ammonium metatungstate (AMT) and NH4VO3 are loaded using an equal-volume impregnation method, with oxalic acid as a complexing agent, and calcined in air at 450-500°C for 4 hours to obtain a fresh V2O5-WO3 / TiO2 SCR catalyst; subsequently, the fresh catalyst is impregnated with an As standard solution and calcined at 500°C for 4 hours to obtain the arsenic poisoning catalyst (As content is determined by ICP-OES). This invention does not impose any specific limitations on the As standard solution or its concentration; any As standard solution well-known in the art that yields the corresponding As content is acceptable.
[0030] In this invention, the mass concentration of the hydrogen peroxide solution is preferably 1-15%, more preferably 5-15%, and even more preferably 10-15% (the optimal concentration was determined to be 15 wt% through single-factor screening experiments at three concentrations of 0, 10, and 15 wt%). The solvent used is preferably water. The pH value of the hydrogen peroxide solution is preferably 7-11, more preferably 9-10, and even more preferably 10. This invention preferably uses NaOH solution to adjust the pH value of the hydrogen peroxide solution (the optimal pH was determined to be 10 through single-factor screening experiments at pH 3, 7, and 10). This invention does not have a specific limitation on the concentration of the NaOH solution; it can be adjusted to achieve the desired pH value as needed.
[0031] In this invention, the solid-liquid ratio of the arsenic poisoning catalyst to the hydrogen peroxide solution is preferably 1g:(5~20)mL, more preferably 1g:(10~15)mL, and even more preferably 1g:15mL.
[0032] In this invention, the diameter of the polytetrafluoroethylene (PTFE) grinding beads is preferably 4-10 mm, more preferably 5 mm. Single-factor screening experiments with diameters of 4, 5, 6, and 10 mm showed that the 5 mm diameter grinding beads exhibited the best performance in terms of arsenic removal rate and catalyst activity recovery.
[0033] The ball milling process described in this invention is preferably carried out in a planetary ball mill, preferably a QM-3SP2 planetary ball mill, with a ball mill jar volume of 100 mL (made of polytetrafluoroethylene). During the ball milling process, the rotation direction is reversed once every 30 minutes to ensure the uniformity of ball milling.
[0034] In this invention, the ball-to-material mass ratio of the polytetrafluoroethylene (PTFE) milling beads to the mixed material is preferably 10-20:1, more preferably 15-20:1, and even more preferably 20:1 (the optimal ball-to-material ratio was determined to be 20:1 through single-factor screening experiments with five ball-to-material ratios of 10, 15, 20, 25, and 30:1); the milling speed is preferably 300-400 rpm, more preferably 350 rpm; and the milling time is preferably 120-180 min, even more preferably 150 min. This invention does not impose any special limitations on the specific process of single-factor screening; any process well-known in the art can be followed.
[0035] During the ball milling process, the PTFE grinding beads and the PTFE grinding jar generate a triboelectric field through contact electrification during collision and friction. Utilizing the PTFE triboelectric field as a natural directional electric field source, the triboelectric field selectively polarizes the diffuse 4s / 4p electron cloud of arsenic, while the compact 3d orbitals of vanadium and the relativistic 5d orbitals of tungsten resist the electric field polarization, thereby achieving selective recognition at the electronic level. Through the synergistic effect of the triboelectric field and mechanical shear force, the As-O poison bond is selectively severed and the condensation and reconstruction of the VOW active bridge bond are simultaneously promoted.
[0036] In this invention, the PTFE-PTFE friction interface between the PTFE grinding beads and the PTFE grinding jar maximizes the triboelectric field, generating a triboelectric field at room temperature without the need for external voltage or heating.
[0037] During ball milling, the collision and friction between the PTFE grinding beads and the PTFE grinding jar produce the following synergistic effects: PTFE, as the most negatively charged material in the triboelectric sequence, generates an interfacial triboelectric field (approximately 0.08 V / Å) at the PTFE-PTFE friction interface through contact electrification during ball milling collisions; arsenic exists as clusters on the catalyst surface, incompatible with the TiO2 lattice; vanadium and tungsten are embedded in the catalyst framework. The mechanical shear force generated by ball milling selectively concentrates at the interface between the arsenic clusters and the framework; the triboelectric field selectively polarizes the dispersed 4s / 4p electron cloud of arsenic, while the compact 3d orbitals of vanadium and the relativistic 5d orbitals of tungsten resist the electric field polarization, thus achieving selective recognition at the electronic level; the superoxide radicals (·O2) generated by the decomposition of hydrogen peroxide (H2O2) under ball milling conditions... -As a soft nucleophile, it selectively attacks the softened As-O bond after polarization, breaking it through a nucleophilic substitution (SN2) mechanism. During the same ball milling collision event, mechanical shear force simultaneously drives the condensation of V-OH and HO-W groups to form VOW bridging bonds (ΔG<0), achieving in-situ reconstruction of the active site. This process is known as the "cleave-and-cap" mechanism. In the collision and friction between the PTFE ball milling beads and the PTFE ball milling jar, the poison cleavage and active site reconstruction are completed simultaneously within a single milling time, eliminating the need for the stepwise "removal-impregnation-calcination" process of traditional methods.
[0038] Through the above methods, this invention establishes the following mechanism: 1) Establish a dual-gating mechanism: Spatial gating (mechanical selectivity): Arsenic is phase-separated in the form of clusters on the catalyst surface, incompatible with the TiO2 lattice; vanadium and tungsten are embedded in the framework. The mechanical shear force generated by ball milling is concentrated at the interface between the arsenic clusters and the framework through the elastic mismatch effect (based on the Eshelby inclusion stress concentration principle).
[0039] Electronic gating (electric field selectivity): Arsenic has dispersed 4s / 4p orbitals, which are easily polarized by an electric field; vanadium's 3d orbitals are compact, and tungsten's 5d orbitals are constrained by relativistic effects and oxygen coordination layers, both resisting electric field polarization. The triboelectric field of PTFE (~0.08 V / Å) selectively softens the chemical hardness of arsenic (HSAB inversion), causing the As-O bond to become ·O2. - Its only pro-nuclear attack target.
[0040] 2) Establishing a "Cleave-and-Cap" synchronous mechanism: In the same ball milling collision event, the mechanical shear force simultaneously cleaves the As-O bond, driving the adjacent V-OH and HO-W groups to condense and form VOW bridging bonds (ΔG < 0, thermodynamically spontaneous). This synchronous reconstruction enables the regenerated catalyst to surpass the performance baseline of the fresh catalyst, rather than recovering to 80-98% as by traditional methods, achieving a super-repair effect that is unattainable by any existing known regeneration method.
[0041] (3) Establish universal criteria
[0042] This invention establishes the concept of a "thermodynamic safety window" through DFT calculations: there is a band gap of 1.88 eV between the As-O bond dissociation energy (~1.7 eV) and the WO skeleton bond (3.58 eV). When the bond energy difference of any poison-skeleton pair exceeds about 1.5 eV, selective surface editing can, in principle, be carried out by the synergistic electro-shearing of the mechanical shearing force generated by PTFE ball milling and the triboelectric field.
[0043] The present invention does not impose any particular limitation on the method of separating the ball milling product from the milling beads; the separation can be carried out in a manner known in the art.
[0044] In this invention, the reagent used for washing is preferably deionized water.
[0045] In this invention, the drying temperature is preferably 100~120°C, more preferably 110°C, and the drying time is preferably 8~16 h, more preferably 12 h.
[0046] The present invention provides a regenerated catalyst obtained by the regeneration method described in the above technical solution.
[0047] The regenerated catalyst obtained by the above regeneration method of the present invention has an arsenic removal rate of ≥90%, preferably ≥92%; the average NO conversion rate in the entire reaction temperature range (200-400 °C) exceeds the baseline of the fresh catalyst by about 35%; the number of strong acid sites in the regenerated catalyst (NH3-TPD determination) exceeds that of the fresh catalyst by more than 90%; the vanadium loss of the regenerated catalyst is lower than the baseline of the vanadium content of the fresh catalyst; and the tungsten retention is comparable to that of the fresh catalyst.
[0048] This invention provides the application of the regenerated catalyst described in the above-mentioned technical solution in the field of denitrification. This invention does not specifically limit the method of application; any method well-known in the art can be used.
[0049] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0050] Unless otherwise specified, the experimental methods described in the various embodiments of this invention are conventional methods; unless otherwise specified, the raw materials used are all commercially available products, and the proportions are all by mass percentage.
[0051] In the following embodiments, the sources of raw materials and equipment are as follows: Arsenic-poisoned V2O5-WO3 / TiO2 SCR catalyst: Laboratory preparation: 4.5 g of anatase TiO2 was weighed, and 0.407 g of ammonium metatungstate (AMT), 0.128 g of NH4VO3 and 0.600 g of oxalic acid were added. After dissolving in 5 mL of water, the solution was impregnated onto a 4.5 g TiO2 support in equal volume. After drying at 105°C, the solution was calcined in a muffle furnace at 500°C for 4 h to obtain fresh catalyst F-VWT (V2O5(1wt%)-WO3(9wt%) / TiO2). Then, the fresh catalyst F-VWT was impregnated with a 10 g / L As standard solution at 60°C for 6 h, dried, and calcined at 500°C for 4 h to obtain arsenic-poisoned catalyst As-VWT (As content determined by ICP-OES was 2.9±0.1wt%).
[0052] Hydrogen peroxide solution (30 wt%, analytical grade, diluted with water to the required concentration and adjusted to the required pH value with NaOH solution before use); Planetary ball mill (model QM-3SP2), with a ball mill jar volume of 100 mL (polytetrafluoroethylene material), and the rotation direction is reversed every 30 minutes during the ball milling process; Polytetrafluoroethylene (PTFE) ball mill jar; Polytetrafluoroethylene (PTFE) grinding beads (5 mm in diameter); Deionized water.
[0053] Performance characterization equipment: X-ray diffractometer (Bruker D8 Advance); specific surface area and porosity analyzer (Micromeritics ASAP 2460); X-ray photoelectron spectrometer (Kratos AXIS SUPRA); electron paramagnetic resonance spectrometer (Bruker EMXplus); chemisorption analyzer (Micromeritics AutoChem 2920, used for NH3-TPD and NO-TPD testing); inductively coupled plasma atomic emission spectrometer (PerkinElmer Optima 8000); laser confocal Raman spectrometer (Horiba LabRAM HR Evolution); Fourier transform infrared spectrometer (Thermo Nicolet iS50); scanning electron microscope (TESCAN MIRA3, equipped with EDS spectroscopy); electrochemical workstation (Bio-Logic VSP-300).
[0054] In the following case, inductively coupled plasma optical emission spectrometry (ICP-OES, PerkinElmer Optima 8000) was used to determine the content of V, W, and As elements. The method detection limits were: As 0.002 μg / mL, V 0.001 μg / mL, W 0.005 μg / mL, and Ti 0.001 μg / mL. Samples were digested with microwave-assisted acid (using a mixed acid system of HNO3 + HF + H2O2) before being tested. Each sample was digested independently and measured in triplicate.
[0055] NO conversion test conditions: 500 ppm NO, 500 ppm NH3, 5 vol% O2, GHSV = 125,000 h - ¹, Quartz reaction tube inner diameter 4 mm, reaction temperature: 200~400℃.
[0056] Example 1
[0057] (1) Weigh 1 g of the above-mentioned arsenic poisoning V2O5-WO3 / TiO2 SCR catalyst As-VWT, add H2O2 solution with a mass concentration of 15% and a pH value of 10 (solid-liquid ratio of catalyst As-VWT to hydrogen peroxide solution 1 g: 15 mL), place the resulting mixture in a PTFE ball mill jar, add PTFE ball milling beads (mass ratio of polytetrafluoroethylene ball milling beads to mixture 20:1), and ball mill in a planetary ball mill at a speed of 350 rpm for 150 min; (2) After ball milling, the grinding balls and the ball milling product are separated. The resulting solid product is washed three times with deionized water and dried at 110°C for 12 hours to obtain the regenerated catalyst, denoted as PTFE-R.
[0058] ICP-OES test results: The As content of the arsenic-poisoned catalyst in Example 1 was 2.9 ± 0.1 wt%, the residual As after regeneration was < 0.2 wt%, and the arsenic removal rate was 92%.
[0059] ICP-OES testing showed that the vanadium loss rate of the regenerated catalyst in Example 1 was 1.7% (the baseline for the fresh catalyst was 2.1%), and the tungsten loss rate was 1.3% (the baseline for the fresh catalyst was 1.4%).
[0060] Example 2
[0061] The only difference between this embodiment and Embodiment 1 is that the ball milling time in step (2) is 60 minutes. This embodiment serves as a control experiment for ball milling time.
[0062] The results showed that the regenerated catalyst achieved an arsenic removal rate of 65% and a NO conversion rate that was restored to 95.3% of that of the fresh catalyst.
[0063] Example 3
[0064] The only difference between this embodiment and embodiment 1 is that the ball milling time in step (2) is 180 min.
[0065] The results showed that the regenerated catalyst achieved an arsenic removal rate of 97% and the NO conversion rate recovered to the level of the fresh catalyst. Vanadium loss increased slightly to 2.0% (close to the aging baseline).
[0066] Example 4
[0067] The only difference between this embodiment and Embodiment 1 is that the mass concentration of the H2O2 solution in step (1) is 5%.
[0068] The results showed that the NO conversion rate was 34.7%, which was slightly higher than that of the fresh catalyst.
[0069] Example 5
[0070] The only difference between this embodiment and Embodiment 1 is that the mass ratio of polytetrafluoroethylene grinding beads to the mixed material is 10:1.
[0071] The results showed that the NO conversion rate was 33.1%, which was close to that of the fresh catalyst.
[0072] Comparative Example 1 (Agate control, no triboelectric field)
[0073] The only difference between this comparative example and Example 1 is that an agate grinding jar and agate grinding balls are used instead of a PTFE grinding jar and PTFE grinding beads.
[0074] The results showed that the NO conversion rate was not significantly improved compared to the fresh catalyst. This control experiment demonstrates that selective regeneration cannot be achieved by mechanical impact alone, and that the triboelectric field is the core element of the method of this invention.
[0075] When agate is used instead of PTFE as the ball milling medium, the collisions generated by agate are mainly impacts and do not produce a significant triboelectric field. The catalyst activity cannot be recovered, thus confirming the necessity of the dual requirements of mechanical selectivity and electronic selectivity for this invention.
[0076] Comparative Example 2 (without H2O2 control)
[0077] The only difference between this comparative example and Example 1 is that in step (1), an equal amount of deionized water is used instead of H2O2 solution.
[0078] The results showed that the NO conversion rate was 38.27%. This control experiment demonstrates that the superoxide radicals generated by the decomposition of H2O2 are a necessary condition for the chemical cleavage of the As-O bond and a condition for the superior performance of the catalyst.
[0079] Comparative Example 3 (H2O2 solution + soaking)
[0080] The only difference between this comparative example and Example 1 is that the arsenic-poisoned V2O5-WO3 / TiO2 SCR catalyst in Example 1 was soaked in H2O2 solution for 3 hours, without the addition of PTFE milling beads or the milling process.
[0081] The results showed that the NO conversion rate was only 4.31% higher than that of the arsenic-poisoned catalyst. This control experiment, which lacked a PTFE control and a triboelectric field, confirmed the crucial role of the PTFE triboelectric field.
[0082] Comparative Example 4 (H2O2 solution + ultrasonic treatment)
[0083] The only difference between this comparative example and Example 1 is that the arsenic-poisoned V2O5-WO3 / TiO2 SCR catalyst from Example 1 was mixed with H2O2 solution and placed in a PTFE ball mill jar, ultrasonically treated at 40KW for 180 min, and PTFE ball milling beads were added, but no ball milling was performed.
[0084] The results showed that the NO conversion rate only recovered to 77.27% of that of the fresh catalyst.
[0085] This comparative example confirms that even if free radicals are generated in the reaction system, the catalytic performance of the poisoned catalyst cannot be fully recovered without the action of triboelectric field and shear force.
[0086] Comparative Example 5 (Treatment of fresh catalyst with PTFE)
[0087] The only difference between this comparative example and Example 1 is that the treatment object is changed to fresh catalyst F-VWT.
[0088] The results showed that the NO conversion rate was 29.7%, which was close to that of the fresh catalyst. This comparative example confirms that the treatment method does not affect the catalyst itself when applied to fresh catalyst.
[0089] Characterization and performance testing
[0090] In the following figures, F-VWT represents fresh catalyst, As-VWT represents arsenic-poisoned catalyst, PTFE-R represents regenerated catalyst, and MN-R represents agate-regenerated catalyst.
[0091] Figure 2 The images show the XRD patterns of the fresh catalyst and the catalyst before and after regeneration in Example 1. Figure 2 The comparison revealed that after arsenic poisoning, the catalyst exhibited diffraction peaks of WO3 crystal clusters.
[0092] Figure 3This is a comparison chart of NO conversion rates for fresh catalyst (F-VWT), arsenic-poisoned catalyst (As-VWT), and catalysts obtained by different regeneration treatment methods in Comparative Examples 1-5 and Example 1. Each sample corresponds to the following: F-VWT is fresh catalyst; As-VWT is arsenic-poisoned catalyst (raw material in Example 1); PTFE-R is PTFE ball-milled regenerated catalyst (Example 1); MN-R is agate ball-milled regenerated catalyst (Comparative Example 1, using an agate ball milling jar and agate ball milling beads instead of PTFE); PTFE-H2O-(As-VWT) is a control regenerated catalyst without H2O2 (Comparative Example 2); H2O2-immersion is a control regenerated catalyst without ball milling treatment (Comparative Example 3); H2O2+ ultrasonic treatment is a control regenerated catalyst (Comparative Example 4); PTFE-R-(F-VWT) is fresh catalyst treated using the method of Example 1 (Comparative Example 5). Figure 3 It can be seen that the NO conversion rate of PTFE-R is significantly higher than that of other regeneration methods, increasing by 65.68% compared to fresh catalyst. The NO conversion rate of MN-R shows no significant improvement compared to the poisoned catalyst, indicating that selective regeneration cannot be achieved solely through mechanical impact. The regeneration effects of Comparative Examples 2 and 3 are also significantly lower than those of PTFE-R, confirming that both H2O2 free radicals and the PTFE triboelectric field are necessary for regeneration. Using a PTFE ball mill jar with ultrasonic treatment of the arsenic-poisoned catalyst (Comparative Example 4), the NO conversion rate did not show a significant change, indicating that the presence of free radicals alone does not improve the low NO conversion rate of the arsenic-poisoned catalyst. Using the method of Example 1 to ball mill the fresh catalyst (Comparative Example 5), the NO conversion rate did not show a significant change, indicating that this treatment method does not adversely affect the catalyst bulk.
[0093] Figure 4 This is a comparison diagram showing the electric field intensity generated during the ball milling process of agate in Comparative Example 1 and polytetrafluoroethylene (PTFE) in Example 1. Figure 4 It is evident that PTFE ball milling generates a significant interfacial triboelectric field (approximately 0.08 V / Å) through contact electrification during the collision process, while agate ball milling, primarily driven by impact, does not produce a significant triboelectric field. This result confirms that the triboelectric field is the core driving force for PTFE ball milling regeneration and the fundamental reason why PTFE-R (with a 65.68% increase in NO conversion compared to fresh catalyst) exhibits superior regeneration performance compared to MN-R.
[0094] Figure 5 NO conversion rates (temperatures 200-400°C) for fresh catalyst (F-VWT) and catalyst before and after regeneration in Example 1. Figure 5It can be seen that, under the test conditions of 250℃, the NO conversion rate of the fresh catalyst F-VWT is 32.08%, the NO conversion rate of the arsenic-poisoned catalyst As-VWT is reduced to 16.93%, and the NO conversion rate of the regenerated catalyst PTFE-R is 97.76%, which is 80.83% higher than that of the arsenic-poisoned catalyst and 65.68% higher than that of the fresh catalyst.
[0095] Figure 6 The amount of ammonia desorption is measured at different temperatures for the fresh catalyst and the catalyst before and after regeneration in Example 1. Figure 6 NH3-TPD analysis showed that the number of strong acid sites in the regenerated catalyst was 89.59 mmol / L. -1 The concentration of fresh catalyst was 45.84 mmol / L. -1 The increase was 95.4%.
[0096] Industrial verification
[0097] Eight types of industrial waste catalysts were collected from eight different coal-fired power plants. All were V2O5-WO3 / TiO2 honeycomb SCR denitrification catalysts. The arsenic content was as follows: GS-W 2.4 wt%, ER-W 0.9 wt%, TG-W 0.158 wt%, PL-W 2.9 wt%, XY-W 2.1 wt%, YM-W 2.3 wt%, SX-W 1.028 wt%, and TRQ-W 0 wt%. The NO conversion rate of each catalyst before regeneration ranged from 12% to 35%. Regeneration was performed according to the method in Example 1, and the results are shown in [Figure 1]. Figure 7 .
[0098] Figure 7 The results showed that after regeneration, the NO conversion rate of all eight catalysts exceeded the baseline of the fresh catalyst, with an increase of 21.2% to 32.2%.
[0099] The regeneration method of the present invention is used for industrial waste catalysts, with a total regeneration cost of $1.48 / kg (including PTFE, H2O2, electricity consumption and labor), which reduces carbon emissions by about 73% compared to the industrial acid washing method.
[0100] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for regenerating an arsenic-poisoned catalyst, characterized in that, Includes the following steps: A mixture of arsenic poisoning catalyst and hydrogen peroxide solution was placed in a polytetrafluoroethylene ball mill jar, polytetrafluoroethylene ball milling beads were added, and the mixture was ball milled to obtain the ball milled product. The ball milling product is separated from the ball milling beads, and the resulting solid product is washed and dried sequentially to obtain the regenerated catalyst.
2. The regeneration method according to claim 1, characterized in that, The hydrogen peroxide solution has a mass concentration of 1-15% and a pH value of 7-11.
3. The regeneration method according to claim 1, characterized in that, The solid-liquid ratio of the arsenic poisoning catalyst to the hydrogen peroxide solution is 1 g:(5~20) mL.
4. The regeneration method according to claim 1, characterized in that, The diameter of the polytetrafluoroethylene grinding beads is 4~10mm.
5. The regeneration method according to claim 1 or 3, characterized in that, The mass ratio of the polytetrafluoroethylene grinding balls to the mixed material is 10~20:
1.
6. The regeneration method according to claim 5, characterized in that, The ball milling process is performed at a rotation speed of 300-400 rpm and for a time of 120-180 min.
7. The regeneration method according to claim 1, characterized in that, The drying temperature is 100~120°C, and the time is 8~16 h.
8. The regenerated catalyst obtained by the regeneration method according to any one of claims 1 to 7.
9. The application of the regenerated catalyst according to claim 8 in the field of denitrification.